Zom-B mission - Shan, Darren (Shan, Darren. Zom-B (Series), 2014)
"B Smith's first mission for the Angels involves relocating human survivors from London to a barricaded community in the countryside. But will the evil influences that enter New Kirkland pose an even greater threat than the living dead outside the barricades?"--